Fostering Inclusive Islam: A Study of Religious Values in Indonesian Language Textbooks at Islamic Higher Education - Sigit Arif Bowo; Sarwiji Suwandi; Andayani Andayani (Jurnal Pendidikan Islam, 2026)
The purpose of this study is to analyze how religious moderation values are portrayed in Indonesian language textbooks used at Islamic Higher Education. Documents from relevant textbooks were analyzed using a qualitative descriptive approach combined with content analysis strategies. The documents analyzed were six Indonesian language textbooks used at the Islamic Higher Education of Central Java Province. Interactive analysis methods were used to analyze the data. Eight fundamental principles of religious moderation are included in the textbooks, according to the findings: 1) fair; 2) deliberation; 3) pioneering; 4) reform; 5) tolerance; 6) nationalism/patriotism; 7) anti-violence; 8) accommodation of local culture. The values that were most commonly portrayed among these were nationalism and the spirit of pioneering. Tolerance, opposition to violence and extremism, and respect for local culture were among the other qualities that were not equally or proportionately incorporated. These books focus more on character building and nationalistic attitudes. Opportunities to create Indonesian language textbooks that more fully and fairly integrate religious moderation values are highlighted by these findings. According to the result, promoting religious moderation in Islamic Higher Education requires balanced content. With Indonesian language textbooks that contain various moderation values proportionally and comprehensively, it is hoped that they can strengthen the spread of moderate attitudes.